Effect of metal cations [Li+, Na+, K+, Be2+, Mg2+, and Ca2+] on the structure of 2‐(3′‐hydroxy‐2′‐pyridyl)benzoxazole: A theoretical investigation. Issue 9 (20th July 2012) - Yi, Pinggui; Liu, Zhengjun; Wang, Zhaoxu; Yu, Xianyong; Zhou, Jiming; Hou, Bo; Li, Qingzhong
Abstract Density functional theory calculations were performed at the B3LYP/6‐311++G(d, p) level to systematically explore the geometrical multiplicity and binding strength for the complexes formed by alkaline and alkaline earth metal cations, viz. Li+, Na+, K+, Be2+, Mg2+, and Ca2+ (Mn+, hereinafter), with 2‐(3′‐hydroxy‐2′‐pyridyl)benzoxazole. A total of 60 initial structures were designed and optimized, of which 51 optimized structures were found, which could be divided into two different types: monodentate complexes and bidentate complexes. In the cation‐heteroatom complex, bidentate binding is generally stronger than monodentate binding, and of which the bidentate binding with five‐membered ring structure has the strongest interaction. Energy decomposition revealed that the total binding energies mainly come from electrostatic interaction for alkaline metal ion complexes and orbital interaction energy for alkaline earth metal ion complex. In addition, the electron localization function analysis show that only the BeO and BeN bond are covalent character, and others are ionic character. © 2012 Wiley Periodicals, Inc.